Determinants of Cardiovascular Disease Risk in the Chronic Disease Management Program at Pasirkaliki Public Health Center, Bandung, Indonesia - Permatasari, Rina Dhyanti; Wahyudi, Yustia Edwina (Althea Medical Journal, 2025)
Background: Cardiovascular diseases (CVDs) are the leading causes of death worldwide and are influenced by multiple risk factors. Stratifying CVD risk using the World Health Organization (WHO) CVD risk charts for Southeast Asia can support routine management, especially for patients with chronic diseases. This study aimed to assess determinants of CVD risk among patients enrolled in the Chronic Disease Management Program at a Public Health Center.Methods: This cross-sectional study was conducted in June 2024 at Pasirkaliki Public Health Center, Bandung, Indonesia. Purposive sampling was applied to select medical records and data was extracted, including age, gender, smoking status, history of diabetes mellitus (DM), systolic blood pressure (SBP), and total cholesterol (TC). CVD risk was stratified using WHO CVD risk classification charts for Southeast Asia. Descriptive and correlation analyses were performed.Results: A total of 124 data patients were collected, with the majority were female adults, non-smokers, had a history of DM with grade 1 hypertension and TC levels between 5.0–5.99 mmol/L. CVD risk stratification showed 43.5% high risk, 25% moderate risk and 16.9% low risk. Interestingly, very high risk was detected in 13.7% and 0.8% was an extremely high risk. Age was strongly correlated with CVD risk (r=0.708, p<0.01), and SBP showed a moderate correlation (r=0.646, p<0.01), whereas TC levels were not significantly correlated (p=0.064).Conclusion: Patient-related factors increase the CVD risk, particularly age and SBP. Routine risk stratification and strengthened chronic disease management program are essential to reduce CVD-related morbidity and mortality.